A Low Creatinine to Body Weight Ratio Predicts the Incident Nonalcoholic Fatty Liver Disease in Nonelderly Chinese without Obesity and Dyslipidemia: A Retrospective Study - Jianxiong Lin; Jiehua Zheng; Xiaoqing Lin; Yexi Chen; Zhiyang Li (Gastroenterology Research and Practice)
Aim. A lower ratio of creatinine to body weight (Cr/BW) is considered the independent risk factor for incident nonalcoholic fatty liver disease (NAFLD). However, the relationship between the Cr/BW ratio and NAFLD among individuals without obesity and dyslipidemia and how this relationship is impacted by age are still ambiguous. Therefore, we explored the effect of the Cr/BW ratio on the incident NAFLD among Chinese without obesity and dyslipidemia of different age groups. Methods. A total of 9756 participants without NAFLD at baseline were included and grouped by the median value (1.32) of the Cr/BW ratio. Then, a further analysis was stratified by age (60 years old). The primary outcome was new-onset NAFLD. Results. After a median follow-up of 2.76 years, 844 (8.7%) participants developed NAFLD. The elderly had a higher person-years incidence rate and cumulative incidence rate than the nonelderly. A high Cr/BW ratio showed a lower cumulative incidence compared to a low Cr/BW ratio for the whole population (P=0.039) and the nonelderly group (P=0.008). After being adjusted for multivariate variables, the lower Cr/BW ratio was the independent risk factor for incident NAFLD in the nonelderly (HR 0.718, 95% CI 0.548-0.942), instead of the elderly. Conclusions. The Cr/BW ratio has a negative relationship with incident NAFLD among nonobese Chinese without dyslipidemia before the age of 60.